FUNCTIONAL RESPONSE OF LARVAL INSTARS OF CHRYSOPERLA CARNEA (NEUROPTERA: CHRYSOPIDAE) FED ON MACROSIPHUM ROSAE (HEMIPTERA: APHIDIDAE) UNDER LABORATORY CONDITIONS - KHAN , SS; SHAH , N; HABIB , A; AKHTAR , H; ULLAH , I; GILL , NJ; REHMAN , A; TAREEN , A (Biological and Clinical Sciences Research Journal, 2024)
The functional response of larval instar of Chrysoperla carnea (Neuroptera: Chrysopidae) fed on rose aphids (Macrosiphum rosae) was investigated to check their predatory potential as biological control agent. This study examined the predation patterns of first, second and third larval instars of C. carnea when exposed to varying densities of rose aphids under controlled laboratory conditions at Department of Entomology, University of Agriculture, Faisalabad. The results showed that all larval stages of C. carnea significantly consumed rose aphids M. rosae. The density of rose aphids (Macrosiphum rosae) had no impact on the functional response of larval instars of green lacewing. Among larval stages, 3rd instar larvae of green lacewing exhibited the highest predation rates on all densities of rose aphids, followed by 2nd and 1st instars. However, aphid consumption rate of larval instars of C. carnea increased with increase in larval stages. Overall, these findings emphasize the significance of larval stages in the predatory performance of green lacewing and highlight the importance of 3rd instar larvae in biological control applications.